TUGAS POKOK DAN FUNGSI SUB BAGIAN TATA USAHA DAN KEPEGAWAIAN DALAM MENDUKUNG FUNGSI DEWAN PERWAKILAN RAKYAT DAERAH (Analisa Studi Pada Sub Bagian Tata Usaha dan Kepegawaian Sekretariat DPRD Guna Mendukung Fungsi Dewan Perwakilan Rakyat Daerah Kota Batu Ja: (Analisa Studi Pada Sub Bagian Tata Usaha dan Kepegawaian Sekretariat DPRD Guna Mendukung Fungsi Dewan Perwakilan Rakyat Daerah Kota Batu) - Anna Patricya Dike Mukin; Yuni Hartono (JOURNAL AKSES STIA MALANG, 2022)
The Regional People's Representative Council (DPRD) is a Regional People's Representative Institutiondomiciled in the Province and Regency/City. In carrying out its functions, DPRD requires assistance from theDPRD Secretariat, another element of administrative service and providing support to DPRD. The Administrationand Personnel Sub-Section are one of the Sub-Sections in Batu City DPRD Secretariat who has the task ofpreparing correspondence and materials for increasing the capacity of human resources of the DPRD Secretariatand members of the Batu City DPRD.The purpose of this study was to find out the duties and functions of the Sub-Division of Administrationand Personnel in supporting the job of the DPRD Batu City and find out what factors were hindering theimplementation of these tasks. This study uses a qualitative descriptive research type. In this study, the primarydata are collected through interviews when the secondary data was through documentation. The informants ofthis study consisted of two subjects, namely the Head of the Sub-Division of Administration and Personnel andthe General Staff and Finance. The data collected were analyzed using a qualitative analysis of the interactivemodel developed by Milles and Huberman in Sugiyono (2019: 322).The results of this study show the main tasks and functions of the Administrative and Personnel SubSection in supporting the job of the Batu City DPRD are preparing materials for coordinating the managementof correspondence, official documents and preparing policy materials for increasing the capacity of humanresources of the DPRD Secretariat and DPRD leaders. The implementations of these tasks have been going well because every employee already understands and has expertise in carrying out the assigned tasks. In carrying outthe duty of supporting the function of the DPRD, there are several obstacles encountered, namely the limitedskilled human resources and the lack of infrastructure.Keywords: Main task and funstions, Sub-Section Administration and Personel, DPRD Function.